Examen especial al componente cuentas por cobrar del hospital básico clínica Latacunga, en el período 2019 - Almachi Mayo, Luis Gregorio (2022)
The purpose of this integrative project was to apply a special examination to accounts receivable of Hospital Básico Clínica Latacunga, in order to determine fair presentation of the account on financial statements, during 2019 period. The used methodology had a quantitative type of documentary and field research and direct observation of the facts. The techniques used were observation, interview and the instruments of an observation sheet and a questionnaire applied to the head of credit and the liquidator - collector. At the process of scientific-technical foundation, legal bases, accounting methods, financial and administrative aspects were reviewed that allowed to know the entity in its internal and external environment, in addition, the interpretation of obtained information at applied interviews was developed same that allowed to determine and indicate the weight of the account receivable in relation to the asset and its importance of special examination, same one that has been carried out according to NIA, analyzed component have been found, among which are: missing records of payments made by clients $ 8,100.00, delinquency and non-payment (patients) in 34.07% of the total receivable accounts, which has caused financial information to present inaccuracies in its preparation.